Assessing the Mediating Role of Social Support in Childhood Maltreatment and Psychopathology Among College Students in Northern Ireland. Issue 3 (February 2021) - Lagdon, Susan; Ross, Jana; Robinson, Martin; Contractor, Ateka A.; Charak, Ruby; Armour, Cherie
The detrimental impact of early trauma, particularly childhood maltreatment, on mental health is well documented. Although it is understood that social support can act as a protective factor toward mental health for children who experience such adversity, few studies have addressed the experience of childhood maltreatment and the important function of social support in adulthood. The current study aimed to assess the mediating role of social support in the relationship between childhood experiences of maltreatment and mental health outcomes including anxiety, depression, posttraumatic stress disorder (PTSD), and problematic alcohol use in a sample of university students ( N = 640) from Northern Ireland. Results of binary logistic regression analyses indicated that those reporting experiences of childhood maltreatment were at increased odds of mental health outcomes of PTSD, anxiety, and depression, but not alcohol use. Those reporting greater social support were significantly less likely to report on these mental health outcomes. In addition, the indirect paths from childhood maltreatment through social support to PTSD, depression, and anxiety were all significant, suggesting that social support, particularly family support, is a significant mediator of these relationships. Such findings have important implications for the social care response to children experiencing maltreatment and future support for such children as they transition to adolescence and adulthood.